Las múltiples caras de Juan Santos Atahualpa - Villanueva Victorio, José Luis (2020)
This article analyzes the three tendencies of scholars when dealing with the historical character Juan Santos Atahualpa: the Franciscan version, the academic version (historical, ethnological, journalistic) and the oral version (collected by Enrique Casanto). Likewise, we distinguish the characteristics of each slope and make a critical evaluation. The objective of the study is to specify the figure of the hero and assess its importance in the history of Peru.